Recovering Connectivity Through Restoration Corridors in a Fragmented Landscape in the Magdalena River's Valley in Colombia (2023)
Forest fragmentation is one of the main drivers of the global decline of biodiversity. This ecological disruption has become pervasive during the last decades, and the emergence of isolated animal populations due to fragmentation, has risen. This study focuses on understanding the role of restoration corridors as a novel strategy promoting the resilience and viability of mammal and bird populations through increasing connectivity in the Middle Magdalena River Valley in Colombia. We installed 82 camera traps to monitor terrestrial and arboreal vertebrates within restoration corridors in a 4000-ha area located in Santander's Department, in Colombia, specifically at Cimitarra Municipality (6°26'40.54'' N 74°7'50.06'' W). Our main goal was to evaluate if mammal and bird species of the tropical humid forests in the Middle Magdalena River in Colombia were using restoration corridors and if restoration corridors were promoting reconnection between communities of terrestrial vertebrates. We completed a sampling effort of 8609 camera-trap days and four sampling sessions, each of 90 days of duration. Cameras were installed in four different scenarios associated with land cover: 1) forest fragments, 2) natural corridors, 3) stablished corridors and 4) pastures. Our findings suggest that there is more species richness in restoration corridors than in pastures, also we could find that the species composition in restoration corridors is beginning to look alike the species composition in forest fragments. Our results provide initial evidence on the role of restoration corridors as an efficient implementation aimed to protect and preserve biodiversity in fragmented landscapes.